A unifying grid approach for solving potential flows applicable to structured and unstructured grid configurations - Kaynak, Ünver; Cete, A. Ruhsen; Yükselen, M. Adil (Elsevier BV, 2008)
zbMATH Open Web Interface contents unavailable due to conflicting licenses.
Keywords: Jets and cavities; cavitation; free-streamline theory; water-entry problems; airfoil and hydrofoil theory; sloshing